Bloodmarked - Deonn, Tracy (New York : Simon & Schuster BFYR, 2022)
"When the leaders of the Order reveal that they will do everything in their power to keep the approaching demon war a secret, Bree and her friends go on the run so she can learn how to control her devastating new powers"--Provided by the publisher.
Junior Library Guild
Ages 14-17.
Grades 9-12.
HL690L
A Junior Library Guild selection
Keywords: Secret societies -- Fiction; Magic -- Fiction; Fantasy